"An Excelent Good Remedi": Medical Recipes as Ethos-Building Tactical Technical Communication in Early Modern England. Issue 4 (2nd October 2022) - Stambler, Danielle Mollie
ABSTRACT: This article examines how nonprofessionals in early modern England used tactical technical communication and rhetorical strategies to build medical knowledge and healthcare expertise. Using a feminist ethos and tactical technical communication lens, this article details a content analysis study of 4, 045 handwritten medical recipes from England dated between 1540 and 1860. Findings from the study extend tactical technical communication by examining non-digital/non-internet spaces and how extra-institutional nonprofessionals build ethos and expertise.